1974
DOI: 10.1029/gm018p0708
|View full text |Cite
|
Sign up to set email alerts
|

Internal gravity-wave motions induced in the earth's atmosphere by a solar eclipse

Abstract: In a solar eclipse, the moon shields a limited region of the earth's atmosphere frSm the heating effect of the solar radiation. This shadow travels through the earth's lower atmosphere at supersonic velocity, causing the neutral gas to emit internal gravity waves that form a bow wave about the shadow region. Tentative estimates of the amplitude of this wave indicate that it will be detectable well outside the area where the eclipse can be observed directly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
80
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 6 publications
5
80
0
Order By: Relevance
“…Anderson et al (1972) reported on surface pressure fluctuations in the range 15-150 min and Seykora et al (1985) found a surface pressure response with a period of about 4 h and a speed of 320 m s −1 . The amplitudes of these waves were larger than those predicted by Chimonas (1970), but agree well with the 0.1-0.5 hPa range modelled recently by Eckermann et al (2007).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Anderson et al (1972) reported on surface pressure fluctuations in the range 15-150 min and Seykora et al (1985) found a surface pressure response with a period of about 4 h and a speed of 320 m s −1 . The amplitudes of these waves were larger than those predicted by Chimonas (1970), but agree well with the 0.1-0.5 hPa range modelled recently by Eckermann et al (2007).…”
Section: Introductionsupporting
confidence: 89%
“…The source of these waves was assumed to be either at higher altitudes e.g. at around 90 km where molecular oxygen heating begins (Chimonas, 1970), or at lower altitude e.g. water vapor IR absorption (Lamb waves) and the ground cooling (Chimonas and Hines, 1971;Chimonas, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several investigations on the Earth's atmospheric and ionospheric effects of SEs [e.g., Boyd, 1966;Anderson et al, 1972;Antonia et al, 1979;Srivastava et al, 1982;Chimonas and Hines, 1970;Chimonas, 1970;Clilverd et al, 2001;Babakhanov et al, 2013 and references therein]. Further studies on SEs ionospheric effects (particularly in lower ionosphere) are warranted because of the fact that each eclipse is different from others based on the occurrence time of the year, time of the day, degree of the solar disk occultation, state of the space, and atmospheric weather and location (latitude and longitude) of observations on the Earth [Baran et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from wide range of implications of SEs on the near Earth's atmosphere and ionosphere, the two most important consequences of SEs are ionospheric variability due to sudden cutoff of solar radiation for a short duration and generation of gravity waves (GWs) [Chimonas, 1970;Zerefos et al, 2007;Babakhanov et al, 2013]. The passage of solar terminator is another main in situ source of GWs.…”
Section: Introductionmentioning
confidence: 99%